2019
DOI: 10.1038/s41401-019-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct ligation enhances AZT CNS toxicity partly by impairing the expression and function of BCRP in rat brain

Abstract: Breast cancer resistance protein (BCRP) is one of ATP-binding cassette (ABC) transporters in brain microvessel endothelial cells that transport their substrates from brain to blood, thus limiting substrates to crossing into brain through blood–brain barrier. Our previous works show that bile duct ligation (BDL) impairs expression and function of brain BCRP in rats. Since zidovudine (AZT) is BCRP substrate, we investigated whether impaired expression and function of BCRP increased brain distribution and toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Liver injury has been demonstrated to alter the expressions and functions of ABC transporters at the blood–brain barrier (BBB). For example, liver injury induced by BDL has been reported to suppress function and expression of Bcrp but enhance the function and expression of P-gp at the BBB of rats [ 18 , 19 , 20 ]. Acute liver injury induced by thioacetamide significantly decreased the expressions and functions of P-gp and Bcrp but increased the expression and function of Mrp2 at the BBB of rats [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liver injury has been demonstrated to alter the expressions and functions of ABC transporters at the blood–brain barrier (BBB). For example, liver injury induced by BDL has been reported to suppress function and expression of Bcrp but enhance the function and expression of P-gp at the BBB of rats [ 18 , 19 , 20 ]. Acute liver injury induced by thioacetamide significantly decreased the expressions and functions of P-gp and Bcrp but increased the expression and function of Mrp2 at the BBB of rats [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that BDL significantly increased the levels of gabapentin in the cortex, hippocampus, and striatum of rats without affecting plasma concentration of gabapentin (Figure 1A); as a result, the brain-to-plasma concentration ratio of gabapentin was significantly upregulated by BDL (Figure 1B). Our previous report showed that BDL has little effect on the integrity of the BBB [36], suggesting that the increased distribution of gabapentin in the brain of BDL rats is attributed to the enhanced function of LAT1. rats (Figure 1E,F).…”
Section: Bdl Increases the Function And Expression Of Lat1 In Brain Tissues Of Ratsmentioning
confidence: 95%
“…BDL rats were developed according to the method previously described in [36]. Shamoperated (sham) rats received the same experimental procedure without bile duct ligation.…”
Section: Development Of Bdl Ratsmentioning
confidence: 99%
“…Cell Culture and Viability Assay hCMEC/D3 cell, an immortalized human cerebral microvascular endothelial cell, is widely utilized as an in vitro BBB model (Qosa et al, 2014;Sánchez-Dengra et al, 2021). It was purchased from FuHeng Cell Center (Shanghai, China) and cultured in RPMI-1640 medium (Invitrogen, Carlsbad, CA, United States) supplemented with 10% fetal bovine serum (FBS) (Invitrogen, Carlsbad, CA, United States) under 5% CO 2 in an incubator (37 °C) as previously described (Qin et al, 2020). For cell viability assay, hCMEC/D3 cells were seeded into 24-well plates at a density of 1×10 5 cells per well.…”
Section: Preparations Of Hepaticmentioning
confidence: 99%